2009
DOI: 10.1017/s1368980008004126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mediterranean Diet Quality Index (KIDMED) in children and adolescents in Southern Spain

Abstract: Objective: The Mediterranean diet is considered one of the healthiest dietary models. Recent changes in the actual Mediterranean diet include a reduction in energy intake and a higher consumption of foods with low nutrient density (e.g. soft drinks, candy, sweets, etc.). In Spain, in association with cultural and lifestyle changes, there has been a reduction in the intake of antioxidants and vitamins, an increase in the proportion of SFA and a decrease in the consumption of fibre, among other changes. Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
0
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 31 publications
13
69
0
23
Order By: Relevance
“…MD adherence widely varied within Mediterranean countries, with large differences also existing among various European countries, while few data are available for non-Mediterranean countries. Similar to our study, studies conducted in Spain, Italy and Greece have confirmed that the majority of children belong to the group of medium adherence to MD (Serra-Majem, 2004;Mariscal-Arcas et al, 2009;Del Mar Bibiloni et al, 2016). To get the insight into the consumption of cereals and bakery products group, the questions dealing with these food groups were extracted from the KIDMED questionnaire and the data obtained are summarized in Fig.…”
Section: Resultssupporting
confidence: 67%
“…MD adherence widely varied within Mediterranean countries, with large differences also existing among various European countries, while few data are available for non-Mediterranean countries. Similar to our study, studies conducted in Spain, Italy and Greece have confirmed that the majority of children belong to the group of medium adherence to MD (Serra-Majem, 2004;Mariscal-Arcas et al, 2009;Del Mar Bibiloni et al, 2016). To get the insight into the consumption of cereals and bakery products group, the questions dealing with these food groups were extracted from the KIDMED questionnaire and the data obtained are summarized in Fig.…”
Section: Resultssupporting
confidence: 67%
“…, 10.30 hours) and their nutrient content. Intakes were evaluated according to previously published guidelines for the Mediterranean diet (7,18,(31)(32)(33) , scoring one point each for the consumption of cereals, fruit/vegetables, dairy products and MUFA fats, one point for the intake of simple sugars ,5 % of total daily energy consumption, one point for energy intake 20-25 % of total daily energy intake, one point for intake of 200-300 mg of Ca, one point for MUFA:SFA ratio above the median for the population, one point for the consumption of cereals, dairy products and fruit/vegetables together in one meal, and one point for the non-consumption of foods rich in SFA or trans fats. Scores on the proposed index scale range from 1 to 10 ( Table 1).…”
Section: Breakfast Quality Indexmentioning
confidence: 99%
“…En concreto en la zona de Levante, la mitad de la población, un 50,2%, entre 2 y 24 años mostraba este grado de adherencia 19 ; datos similares a los encontrados en este estudio inicialmente, donde un 58,33% de la muestra también tiene un índice Kidmed entre 4 y 7. Además, en estudios realizados con niños de mayor edad se observa que al aumentar la edad disminuye la adherencia 11,[20][21][22][23] . Aunque de manera no significativa, en este estudio se ha producido tras las intervenciones un aumento en la adherencia a la Dieta Mediterránea.…”
Section: Discussionunclassified
“…Relacionándose una elevada adherencia a la Dieta Mediterránea con una baja mortalidad y un efecto protector frente enfermedades cardiovasculares, diabetes tipo 2 y algún tipo de cáncer [6][7][8][9] . Este conjunto de beneficios contrasta con una disminución de su seguimiento, lo que justifica su promoción entre la población 10,11 . Anteriores estudios ponen de manifiesto que pequeñas intervenciones nutricionales realizadas en la escuela, contando con la colaboración de profesores y padres, mejoran los conocimientos sobre alimentación o los hábitos alimentarios 12,13 .…”
Section: Introductionunclassified